Targeting of genomic and negative‐sense strands of viral RNA contributes to antiviral resistance mediated by artificial miRNAs and promotes the emergence of complex viral populations. (21st August 2022) - Mesel, Frida; Zhao, Mingmin; García, Beatriz; Simón‐Mateo, Carmen; García, Juan Antonio
Abstract: Technology based on artificial small RNAs, including artificial microRNAs (amiRNAs), exploits natural RNA silencing mechanisms to achieve silencing of endogenous genes or pathogens. This technology has been successfully employed to generate resistance against different eukaryotic viruses. However, information about viral RNA molecules effectively targeted by these small RNAs is rather conflicting, and factors contributing to the selection of virus mutants escaping the antiviral activity of virus‐specific small RNAs have not been studied in detail. In this work, we transformed Nicotiana benthamiana plants with amiRNA constructs designed against the potyvirus plum pox virus (PPV), a positive‐sense RNA virus, and obtained lines highly resistant to PPV infection and others showing partial resistance. These lines have allowed us to verify that amiRNA directed against genomic RNA is more efficient than amiRNA targeting its complementary strand. However, we also provide evidence that the negative‐sense RNA strand is cleaved by the amiRNA‐guided RNA silencing machinery. Our results show that the selection pressure posed by the amiRNA action on both viral RNA strands causes an evolutionary explosion that results in the emergence of a broad range of virus variants, which can further expand in the presence, and even in the absence, of antiviral challenges. Abstract : The negative‐sense RNA strand of positive‐sense RNA viruses is cleaved by the amiRNA‐guided RNA silencing machinery, and selection pressure posed by amiRNA action on both viral RNA strands conditions the emergence of a broad range of escape mutant viruses.